ORGANIZATIONAL AND STRUCTURAL SUPPORT OF THE STATE REGULATION OF SOCIAL PROTECTION OF PARTICIPANTS OF THE ANTI-TERRORIST OPERATION - Kondratenko O.О. (Pressing Problems of Public Administration, 2018)
The article focuses on the problems of the social sphere, state regulation of social protection of theparticipants of the Anti-Terrorist Operation in the east of Ukraine. The main aspects of organizationaland structural support are considered. The functions of the authorities of general and specialcompetence involved in resolving the range of social protection issues of the Anti-Terrorist Operationparticipants at both central and local levels have been designated.